Implementasi Metode AHP dan SAW Menentukan Kreasi Inovasi Daur Ulang Terbaik Pada Bank Sampah - Safitri, Mayang; Fakhriza, M; Dedi Irawan, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Waste remains a significant problem in the city of Medan, even in Indonesia. Dealing with waste in the city of Medan continues to be a major task for anyone responsible for its management. However, waste can be turned into creative and innovative recycling projects that can be competed in and always be present in events related to the environment. Waste banks serve as a platform for organizing recycling competitions, but differences in priority criteria, participant data storage, and a lengthy assessment process pose challenges. Decision Support Systems (DSS) offer a solution to this issue. This research aims to identify participants deserving of winning the best recycling creativity and innovation competition. The method used to determine priority weights is the Analytical Hierarchy Process (AHP), and to rank the competition participants, the Simple Additive Weighting (SAW) method is employed.